PENGARUH METODE PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Ms. Edora (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2017)
This research is conducted to reveal the influence of Problem Based Learning method toward students’ critical thinking ability improvement on Introduction of Economy and Business subject in SMKN 1 Bandung. The method used in this research is quasi experimental with Nonequivalent (Pretest and Posttest) Control Group Design. The data analysis technique with parametric statistical, test of difference (paired samples t-test and independent samples t-test), gain score and effect size calculation used in this research is SPSS versi 21. The result shown that the use of Problem Based Learning method is more effective to improve the critical thinking ability than the Jigsaw techniques. learning